Analysis Analisis Efektivitas Program Penyuluhan Hukum dalam Menekan Penyakit Masyarakat dan Kenakalan Remaja di Kota Bogor - Andri Brawijaya; Henny Nuraeny (Faculty of Law, Maranatha Christian University, 2025)
Legal awareness is a crucial factor in preventing the emergence of social ills and juvenile delinquency. The phenomena of drug abuse, promiscuity, brawls, and various other forms of deviant behavior reflect a weak understanding and compliance with legal norms among the community, especially the younger generation. This low legal awareness not only has an impact on increasing the potential for legal violations, but also threatens social order and security stability in the community. This study focuses on two main problems, namely (1) the factors causing low legal awareness in the community, and (2) a conceptual model of legal awareness that can be applied to prevent deviant behavior. The purpose of this study is to identify the determinants that influence low legal awareness and to formulate a collaboration-based legal awareness model that can be implemented in an integrated manner by the government, law enforcement officers, educational institutions, community leaders, and families. The method used is a literature study with a qualitative approach through analysis of literature, laws and regulations, and the results of relevant previous research. The results of the study indicate that low legal awareness is influenced by the low level of legal education in the community, weak social control functions of families, minimal involvement of religious and community leaders in moral development, and inconsistency in law enforcement. The proposed conceptual model emphasizes early legal education, strengthening the role of the family, optimizing religious and social activities, increasing persuasive public campaigns, and implementing firm but humane law enforcement.